International Private And Mixed Jurisdiction - Hussain Abd Ali Issa; Shirwan Ali Mahmood (QALAAI ZANIST JOURNAL, 2020)
The question of the gravity and the control of the most serious international crimes, Called for efforts to find appropriate solutions to reduce the seriousness and impunity of the perpetrators, One of which is to give jurisdiction to the special temporary international tribunals established by a resolution of the Security Council, As well as the establishment of mixed courts. This paper deals with these two types of international criminal tribunals by stating their terms of reference and clarifying their shortcomings and making the necessary recommendations to avoid such defects.